Inhibition of erythrocyte sickling in vitro by DL-glyceraldehyde. - Nigen, A M (1977)
Concentrations of DL-glyceraldehyde between 5 and 20 mM reduce the sickling of S/S erythrocytes even in the complete absence of oxygen; at 10 mM glyceraldehyde the increase in the number of normal cells ranges from 20 to 40%. The inhibition of sickling was both concentration- and time-dependent and was not reversed by repeated washings with buffer. Incubation of erythrocytes with increasing concentrations of glyceraldehyde resulted in only a small increase in the oxygen affinity, a moderate reduction in the Hill coefficient, a substantial increase in the minimum gelling concentration, and modification of up to two lysine residues per hemoglobin molecule.